Seroprevalence and risk factors associated with leptospirosis in dogs - Meeyam T. (2014)
This study was done to determine the seroprevalence and risk factors of leptospirosis in dogs. From March to September 2004, a total of 210 dogs were randomly selected from the Small Animal Hospital, Faculty of Veterinary Medicine, Chiang Mai University. Dog sera were collected from the cephalic vein and kept at -20 degrees C until submitted to the National Institute of Health for a Microscopic Agglutination Test (MAT). Risk factors were analysed using logistic regression modelling. The prevalence of Leptospira antibodies was 11% (23/210). The most prevalent Leptospira serogroups were Bataviae 5.2% (11/210), Canicola 2.4% (5/210), Australis 1.4% (3/210), Icterohaemorrhagiae 1.4% (3/210), Ballum 0.5% (1/210), Djasiman 0.5% (1/210), Javanica 0.5% (1/ 210), Mini 0.5% (1/210), and Sejroe 0.5% (1/210). Risk factors, including signalment, environment and health status, were not significantly associated with leptospirosis antibodies. However, playing in sewage, staying outdoors >50% of the time, and consumption raw meat increased the risk of leptospirosis antibodies in dogs.